Integrated Reporting Disclosure: Voluntary Perspectives - Rizdina Azmiyanti; Helmy Sukiswo (Future Science, 2021)
The study aims to analyze the integrated reporting disclosure in the IR framework from a voluntary perspective. The method uses several keywords to find 5 related articles to be reviewed. Journal database uses science direct and emerald/ this study found that South Africa has the rule to publish integrated reporting is mandatory, while other countries did not. It is found that an overview of organizations and risk and opportunity became the highest element to be disclosed while the basis of presentation and preparation was not completely disclosed. However, several researchers explained that they got an advantage using integrated reporting even though there are no rules to publishing integrated reporting. The report has the advantage to provide new insight into the combination of financial and non-financial reporting. This research will have to contribute to providing a regulation to publish the integrated reporting and organizations can consider publishing integrated reporting to make a good relationship with stakeholders for creating value.